Pemberdayaan Siswa SMK Bina Dharma Melalui Pembuatan Serbuk Effervescent sebagai Produk Kesehatan Berbasis Etnofarmasi: Empowering Bina Dharma Vocational School Students Through the Production of Effervescent Powder as an Etnopharmacy-Based Health Product - Liza Pratiwi; Bambang Wijianto; Muhammad Akib Yuswar; Muhammad Nur Ajwad; Fakhruddin Fakhruddin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Vocational education that combines theory and practice has been proven to be effective in improving students' skills, particularly in preparing them for the challenges of the working world. This study aims to evaluate the effectiveness of the materials and practices used in the production of effervescent moringa powder on students' understanding at SMK Bina Dharma Pratama. The research design used was quasi-experimental with a one-group pretest-posttest design. The study began with a pre-test to assess students' initial knowledge, followed by the provision of materials and practical training in the production of effervescent moringa powder. After the activities, the students were given a posttest to measure their increased understanding. The study's results showed an average score increase from 53.75 (pre-test) to 63.75 (post-test), or approximately 18.6%. This increase indicates a significant learning gain. Despite variations in student results, this finding suggests that practice-based learning can enhance students' technical skills and conceptual understanding in pharmacy. This study contributes to the development of educational methods that integrate theory and practice to enhance students' practical skills and to the implementation of experiential education in vocational training.